Administrative resolution No. 94/2014 With Regard to Announcing in Al-Wakaye Al-Mesreya / Government bulletin the Amendments Related to A Set of Egyptian Standard Specifications Concerning Which Binding Ministerial Decrees Were Previously Issued = قرار إداري رقم 94 لسنة 2014 بشأن الإعلان بجريدة الوقائع المصرية عن تعديلات على مواصفات قياسية مصرية سبق صدور قرارات وزارية ملزمة لها / the Egyptian organization for standardization and quality - Egypt. the egyptian organization for standarization and quality (2025)
The Egyptian Organization for Standardization and Quality Administrative Resolution no. 94 of the year 2014 with regard to announcing in Al-wakaye Al-Mesreya Administrative Resolution No. 94/2014 With Regard to Announcing in Al-Wakaye Al-Mesreya / Government bulletin the Amendments Related to A Set of Egyptian Standard Specifications Concerning Which Binding Ministerial Decrees Were Previously Issued الهيئة المصرية العامة للمواصفات والجودة قرار إدارى رقم 94 لسنة 2014 بشأن الإعلان بجريدة الوقائع المصرية عن تعديلات على مواصفات قياسية مصرية سبق صدور قرارات وزارية ملزمة لها